Effectiveness of Added L-Ascorbyl Palmitate Antioxidant Synthezed Enzymatically in Coconut Oil - Tri Agus Siswoyo; Martiyas Pujirahayu (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
L-ascorbyl palmitate (AsA-Pal-Enz) was synthesized by using the immobilized lipase from Aspergillus niger. The antioxidative activity of AsA-Pal-Enz was investigated in coconut oil at different temperatures within a range of 30(RT)-120oC. The effectiveness of AsA-Pal-Enz in coconut oil was monitored by the rate of formation of hydroperoxides, conjugated dienes (K232) and decomposition of hydroperoxides (K270). Samples in storage experiments were periodically removed and analyzed for peroxide value, K232, K270 and radical scavenging activity (DPPHr). Application of AsA-Pal-Enz have markedly reduced the rate of peroxidation in coconut oil during incubation time at RT, 60 and 80oC but at 120oC the rate of peroxidation slightly increased. It has shown that the effectiveness of AsA-Pal-Enz antioxidant in coconut oil was strongly depend on temperature and the time of incubation.